Pancasila as a Legal Pillar in Ensuring Human Rights Protection - Soraya, Joice; Muslim, Shohib (Lex Journal: Kajian Hukum & Keadilan, 2025)
This study aims to examine the role of Pancasila as a legal pillar in ensuring the protection of human rights in Indonesia, especially after the amendment of the 1945 Constitution (UUD 1945) in 1999-2002. The main focus of this research is to identify how the values of Pancasila can be applied in the context of the rule of law to protect the basic rights of every individual and how Pancasila functions as the basis of the state in respecting human rights, as well as how the amendments to the 1945 Constitution strengthen the sovereignty of the people and the protection of these basic rights. This research uses normative legal research methods by analyzing constitutional texts, laws, and other scientific literature. The discussion covers the relationship between Pancasila, popular sovereignty, the rule of law, and human rights, as well as the implementation of Pancasila principles in Indonesian legal policy. The conclusion of this study shows that Pancasila still plays an important role as the main foundation in realizing a rule of law that focuses on the protection of human rights and people's sovereignty, as well as guidelines in the development of a fair and democratic legal system.